Faktor Terjadinya Ketuban Pecah Dini pada Ibu Bersalin di Rumah Sakit Umum Daerah Rokan Hulu 2011 - Sepduwiana, Heny (Jurnal Martenity and Neonatal, 2013)
Premature rupture of membranes is rupture of membranes before inpartu. The premature rupture can be caused by several factors such as the location of abnormalities of the fetus, multiple pregnancy, congenital abnormalities of the membranes, pelvic abnormalities, The purpose of this study was to describe the factors premature rupture of the maternal in the General Hospital of Rokan Hulu in 2011 , by age and parity. The research method is descriptive type of cross-sectional design, with secondary data from a medical record General Hospital Rokan Hulu. The results of this study based on the age of 20-35 years the incidence of premature rupture of membranes, namely 76 (82.6%). On the number of parity 0premature rupture incidence is 45 people (48.9%).